2019
DOI: 10.22236/jkpuhamka.v2i2.4868
|View full text |Cite
|
Sign up to set email alerts
|

Visionary Leadership and the Self Efficacy With Organizational Commitment

Abstract: The aims of this study is to identify and analyze the relationship between school principal visionary leadership and teacher’s self-efficacy toward teacher’s organizational commitment. The study used a survey method. Population of 223 teachers, and a sample of 143 teachers. Data collected by questionnaire technique. Data analyzed with correlation and regression techniques. The results showed that: 1) there is a positive and significant relationship between the visionary leadership of the head teacher of the sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
1
3
0
Order By: Relevance
“…Islamic visionary leadership has a direct influence on organisational commitment, which means that if a leader has a Islamic visionary leadership style, there will be an increase in employee commitment to the organisation. This study supports the results of Yates et al (2018), Basri et al (2021), Isma et al (2018), Kesumayani et al (2020), Pulungan et al (2019) and Syarif and Lina (2019) that there is a significant relation between Islamic visionary leadership and organisational commitment.…”
Section: H1: the Effect Of Islamic Visionary Leadership On Organisati...supporting
confidence: 90%
See 2 more Smart Citations
“…Islamic visionary leadership has a direct influence on organisational commitment, which means that if a leader has a Islamic visionary leadership style, there will be an increase in employee commitment to the organisation. This study supports the results of Yates et al (2018), Basri et al (2021), Isma et al (2018), Kesumayani et al (2020), Pulungan et al (2019) and Syarif and Lina (2019) that there is a significant relation between Islamic visionary leadership and organisational commitment.…”
Section: H1: the Effect Of Islamic Visionary Leadership On Organisati...supporting
confidence: 90%
“…Kesumayani et al (2020) revealed in their research that Islamic visionary leadership has a positive and significant impact on employee commitment to the organisation, supported by Pulungan et al (2019) in their research that Islamic visionary leadership has a positive and significant impact on employee commitment to the organisation. Likewise, Syarif and Lina (2019) stated in their research that Islamic visionary leadership has a positive and significant impact on employee commitment to the organisation. Kurniadi et al (2020) suggested that Islamic visionary leadership has a positive and significant effect on employee performance.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Organizational commitment refers to the willingness of employees to voluntarily accept the values and goals of the organization, and to then identify those values and goals in their job responsibilities (Suharto & Hendri, 2019). For Syarif and Lina (2019), organizational commitment is related to the strength of employees in determining their involvement in parts of the organization. In addition, it also reflects a feeling of belonging to the organization (Diana et al, 2022).…”
Section: Organizational Commitment and Organizational Citizenship Beh...mentioning
confidence: 99%